2018
DOI: 10.4236/abb.2018.97020
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Multi-Drug Resistant Bacteria from Hospital Wastewater Sites around the City of Aizawl, Mizoram

Abstract: A microbial study was conducted from wastewater soils of hospitals in Aizawl, Mizoram, India which were in existence for a longtime. The isolated bacteria from the wastewater soils were found to be mainly of Morganella morganii and Bacillus cereus and these isolated bacteria were found to be very resistant to a wide range of antibiotics and heavy metals. Antibiotics that were used for treating infections caused by these bacteria like chloramphenicol and ciprofloxacin were also found to be insensitive. The degr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
(13 reference statements)
0
3
0
Order By: Relevance
“…In this present study, least resistance by Morganella morganii (20%) was observed. M. morganii are intrinsically resistant to members of beta-lactam but are known to be susceptible to large group of antibiotics such as fluoroquinolones (ciprofloxacin), aminoglycosides, chloramphenicol, cephalosporins, aztreonam [45]. In this study, other isolates that exhibited multidrug resistance are P. mirabilis and K. pneumoniae (70% each), S. enteric (60%), C. fruendii (50%), and Vibro cholera (40%).…”
Section: Discussionmentioning
confidence: 77%
“…In this present study, least resistance by Morganella morganii (20%) was observed. M. morganii are intrinsically resistant to members of beta-lactam but are known to be susceptible to large group of antibiotics such as fluoroquinolones (ciprofloxacin), aminoglycosides, chloramphenicol, cephalosporins, aztreonam [45]. In this study, other isolates that exhibited multidrug resistance are P. mirabilis and K. pneumoniae (70% each), S. enteric (60%), C. fruendii (50%), and Vibro cholera (40%).…”
Section: Discussionmentioning
confidence: 77%
“…Sewage is the byproduct of water characterized by physical, chemical, and bacteriological contaminants. Uncontrolled and excessive use of antibiotics by human cause increase in multidrug resistance in hospital effluents (Hauhnar et al, 2018). One milliliter of sewage typically contains between 10 5 and 10 6 microorganisms (Shchegolkova et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of such pollutants would continue to favour the development of resistance as the pathogens can easily donate the genes responsible for the upsurge of resistance in a microbial community. This phenomenon is aided by mobile genetic elements like plasmids and transposons in a horizontal manner [48,49]. Exchange of genetic contents between bacteria is common as a survival strategy; Bridget et al [50] detected recurrent conjugative transfer of resistant genes in the 83% of environment isolates that had exchanged one or more resistant genes.…”
Section: Behaviouralmentioning
confidence: 99%